Foods and Supplements Associated with Vitamin B(12) Biomarkers among Vegetarian and Non-Vegetarian Participants of the Adventist Health Study-2 (AHS-2) Calibration Study - Damayanti, Didit (Nutrients, 2018)
To investigate the association between plasma concentration of vitamin B(12) and B(12) intake from supplements, fortified foods, and animal source foods among vegetarians and non-vegetarians, we conducted a cross-sectional analysis among 728 participants of the Adventist Health Study 2 (AHS-2) calibration study. The median age of participants was 58 years, 65.4% were female, and 50.3% were White. We used six 24 h dietary recalls to measure B(12) intake, serum vitamin B(12), and holotranscobalamin (holoTC) concentration. B(12) supplements had a significantly positive association with plasma B(12) among all subjects (p trend < 0.001), especially among vegans and lacto-ovo vegetarians (p trend < 0.001). Among non-users of B(12) supplements, B(12) intake from milk substitutes was significantly positively associated with holoTC (p trend < 0.004) and serum B12 (p trend < 0.030). In non-vegetarians, holoTC was significantly positively associated with B(12) intake from eggs, while serum B(12) was significantly positively associated with B(12) intake from milk in the upper tertile compared to the lower, and B(12) intake from meat in the middle compared to the lower tertile intake (p < 0.011). Supplements containing B(12) followed by B(12) intake from milk substitutes were significant contributors of plasma vitamin B(12) concentration.